Feasibility of using zein in gluten-free baking - Bloom, Rachel (Kansas State University, 2015)
Flour is essential to bread production as it provides structure, texture, and flavor. The most common, wheat flour, is unique compared to other cereal flours as it forms gluten that is capable of forming viscoelastic dough, which retains gas produced during fermentation and helps create cohesive dough, all of which are critical to bread development. However, a certain percentage of the population has a rare autoimmune disorder, celiac disease, which is triggered by gluten. A gluten-free diet is the only remedy for celiac disease. Traditionally, in gluten-free breads, hydrocolloids, or gums have been used to mimic the behavior of gluten. However, the lack of a protein structure in breads made with hydrocolloids leads to an almost batter-like viscosity. Therefore, research has focused on gluten-free alternatives, particularly non-wheat cereal proteins that can be altered to mimic gluten’s dough forming properties. For example, zein has an average molecular weight and larger peptides than gluten, which contribute to its hydrophobic behavior. In fact, zein from maize flour is an ideal alternative as it can be manipulated to behave like gluten under certain conditions. The main difference between gluten and zein is that zein does not exhibit a large disulfide-linked polymer. Zein is also more hydrophobic than gluten. However, zein has been found to exhibit viscoelastic properties similar to gluten’s at temperatures higher than its glass transition. Other research has found the secondary structure of zein, in particular the β-sheet structure, increases at temperatures above its glass transition. This suggests that temperature and shear are not the only factors necessary to form and maintain the viscoelastic properties of zein; apparently, the β-sheet structures also affect viscoelasticity. Finally, differences such as maize variety and particle size also affect the properties of zein in bakery applications.
Keywords: Zein; Gluten free; Maize; Food Science (0359)